CUSTOMER RELATIONSHIP MANAGEMENT TOOLS AND ORGANIZATIONAL PERFORMANCE OF COMMERCIAL BANKS IN SOUTHWEST, NIGERIA - Bolaji Comfort ADENIYI; Gbenga Sunday FAYIGBE (Malete Journal of Accounting and Finance)
The purpose of the study was to examine the extent at which customer relationship management tools influence the organizational performance of commercial banks in Southwest, Nigeria. The study was carried out using the descriptive research design of the survey type. The population of the study was six hundred and twenty-four (624) respondents which comprised all the zonal/branch, operations, human resources manager and customer care giver of five of each of the twenty-six (26) commercial banks in Southwest, Nigeria, (CBN, 2024). The sample of the study consisted of three hundred and ninety (390) respondents which was achieved through multistage sampling techniques. The study adopted a questionnaire instrument tagged ‘Customers Relationship Management Tools and the Organizational Performance of Commercial Banks’ (CRMPB). The reliability of the instrument was estimated at 0.80 using Chronbach’s Alpha reliability method. The data collected for this study was analyzed using both descriptive and inferential statistics. All hypotheses were tested at 0.05 level of significance. This study revealed that there is significant relationship between the usage of customer relationship management tools and the organizational performance of commercial banks operating in Southwest, Nigeria; there is significant relationship between Hub Spot CRM tools and customer retention rate of commercial banks operating in Southwest, Nigeria, and there is significant relationship between Oracle CX Cloud CRM tools and cross-selling and upselling opportunities in commercial banks operating in Southwest, Nigeria. Based on the findings of the study, it was recommended that commercial bank operators should adopt the usage of CRM tools to enhance their organizational performance.